Characterization of Energy Quality in incandescent, Fluorescent, Induction and LED bulbs (Ciencias de la Ingeniería y Aplicadas, 2022)
The study of energy quality, using different types of lighting such as incandescent, LED, fluorescent and energy savers, which generate different distortions in the waveform of both voltage and current to the network, causing negative performance in the different types of lighting. machines that are connected to it, as well as poor technical performance of the quality of the energy supplied that affects the lighting systems, reducing their useful life, as a result of flickering or electrical flickers, blackouts, among others. Currently in our country these types of products are being widely marketed, which are characterized by energy savings regardless of the effect on the quality of the energy and without meeting the minimum requirements to guarantee the same technical and constructive quality as In many cases they do not comply with current regulations. It is pertinent to consider that the change in the Energy Matrix based on both the constitution of the Republic of Ecuador promulgated in 2008 guarantees through its articles 15, 313, 314, 413 the efficient use of energy and establishes the import standard of these lighting equipment, which makes it necessary to carry out a study of energy quality and its impact on the network, especially due to the low power factor and harmonics that may occur. in the electrical system. Through a technical, experimental and analytical study, the behavior of the electrical parameters presented by the different LED, fluorescent and incandescent lamps that are currently marketed in the Ecuadorian market is established in order to establish compliance with the specifications that they endorse as efficient products that guarantee energy efficiency.
Keywords: Harmonics; Energy efficiency; Power Quality; Energy Matrix